Physical activity and sedentary behavior levels among individuals with mental illness: A cross-sectional study from 23 countries. - Fernanda Castro Monteiro; Felipe de Oliveira Silva; Aline Josiane Waclawovsky; José Vinícius Alves Ferreira; Fabianna Resende de Jesus-Moraleida; Felipe Barreto Schuch; Philip B Ward; Simon Rosenbaum; Rachel Morell; Lara Carneiro; Andrea Camaz Deslandes (PLoS ONE, 2024)
People with mental illness tend to present low levels of physical activity and high levels of sedentary behavior. The study aims to compare these levels in mental illness patients, exploring the role of socioeconomic development and treatment setting. This cross-sectional study used accelerometers and the Simple Physical Activity Questionnaire (SIMPAQ) to assess physical activity and sedentary behavior in mental illness individuals living in 23 countries. Two-way ANOVAs were used to evaluate the interaction between socioeconomic development and the treatment settings on physical activity and sedentary behavior. A total of 884 (men = 55.3%) participants, mean age of 39.3 (SD = 12.8), were evaluated. A significant interaction between socioeconomic development and treatment settings was found in sedentary behavior (F = 5.525; p = 0.019; η2p = 0.009; small effect size). Main effects were observed on socioeconomic development (F = 43.004; p < 0.001; η2p = 0.066; medium effect size) and treatment setting (F = 23.001; p < 0.001; η2p = 0.036; small effect size) for sedentary behavior and physical activity: socioeconomic development (F = 20.888; p < 0.001; η2p = 0.033; small effect size) and treatment setting (F = 30.358; p < 0.001; η2p = 0.047; small effect size), showing that HIC patients were more active, while MIC patients were more sedentary. Moreover, despite of inpatients had presented higher levels of physical activity than outpatients, they also spent more time sitting. Socioeconomic development plays an important role in sedentary behavior in patients with mental disorders, warning the need to develop new strategies to reduce these levels in this population.